Revealing the Subtle Interplay of Thermal and Quantum Fluctuation Effects on Contact Ion Pairing in Microsolvated HCl. Issue 4 (19th November 2012) - Walewski, Łukasz; Forbert, Harald; Marx, Dominik
Abstract The combined effect of thermal fluctuations and quantum mechanical motion on the HCl(H2O)4 cluster is studied at different temperatures. Two conformations of this cluster are investigated: the ringlike structure that involves an undissociated HCl molecule (UD) and the contact ion pair (CIP), which involves the dissociated acid, Cl−, and H3O+. The UD structure is affected by thermal and quantum fluctuations in a similar way. The hydrogen‐bond network is destabilized, and this results in ring expansion and proton orientational rearrangements, though the thermal excitation prevails over the quantum effects at high temperature, while the zero‐point motion dominates in the low‐temperature regime, as expected. In contrast, the thermal and quantum fluctuations exert competing effects on the CIP structure. At high temperature one of the hydrogen bonds accepted by Cl− breaks, and this results in undercoordination of the Cl site, which leads to proton transfer along the fluxional Cl−⋅⋅⋅H3O+ hydrogen bond and formation of molecular HCl. Thus, thermal fluctuations counteract acid dissociation and thus ion‐pair formation. At low temperature however, the decreasing thermal excitations facilitate recovery of the full hydrogen‐bond network, which pushes the proton away from the Cl site and thus leads to acid dissociation, which characterizes the equilibrium structure. On the other hand, quantum mechanical fluctuations, which destabilize the hydrogen bonds supporting the Cl− ion and pull the proton back towards the undissociated limit, become of overriding importance in the low‐temperature limit. As a result, the subtle balance between the two trends enables temperature‐dependent "low‐barrier hydrogen bonding" and establishes a centered hydrogen bond, H2O⋅⋅⋅H+⋅⋅⋅Cl−, at intermediate temperatures.